SPATIAL MODEL OF PUBLIC NON-IONIZING RADIATION EXPOSURE ON SELECTED BASE STATION AROUND KUALA NERUS - Roslan, Umar; A. R. S. N., Dianah; S. N., Hazmin (2018)
Although it is not as intense as in other countries around the world, Malaysia is not left out to enhance the rapid development of technology by installing thousands of base station tower as an initiative to support the advancement of technologies nowadays. The construction of more base stations tower either for telecommunication, broadcasting or other systems has caused public concern about the possibility of adverse health effects on residents nearby due to NIR exposure emitted. This study is conducted to study the NIR exposure level around selected BST in Kuala Nerus. The NIR exposure level was detected using spectrum analyzer through circular patch (CP) antenna, which is specifically developed for this study. Spatial model of NIR exposure was developed using Geographic Information System (GIS) technique so the interpretation of NIR exposure level from BST for Kuala Nerus can be obtained.